Effect of Changes in the Concentrations of Sodium Chloride, Sodium Bicarbonate, and Citric Acid on the Surface Tension and Viscosity of Solutions of Certain Polymers - Najla Ali Elgheryani (Al-Mustansiriyah Journal of Science)
Background: The polymer’s improved properties enable its application in numerous fields. Different concentrations of sodium chloride (NaCl), citric acid (C6H8O7), and sodium bicarbonate (NaHCO3) were added to aqueous solutions of the following polymers: Polyacrylamide (PAM), Polyanionic cellulose low viscosity (PACLV), Carboxymethylcellulose low viscosity (CMCLV), and Polyethylene glycol (PEG) and Polyvinylpyrrolidone (PVP), It was added to know the effect of the additives on the polymers of the samples studied and which ones improve the properties of the polymers more than others. Objective: The objective of this work is to improve certain physical properties of the polymers used in the samples. Methods: The weights of the droplets of the solutions were measured, and the time of its flow. Surface tension and surface tension force and energy were calculated, and relative viscosity, specific viscosity, reduced viscosity, inherent viscosity, and intrinsic viscosity were calculated. Results: The results obtained indicate an increase in the surface tension, where the change in concentrations of citric acid (C6H8O7) caused the largest increase to the surface tension of the solutions, while the surface tension of the solutions increased less when changing the concentrations of NaHCO3 and the increase in surface tension in the case of changing the concentrations of NaCl was less than changing the concentrations of both C6H8O7 and NaHCO3. Also, the relative viscosity of the polymer solutions increased. Conclusions: The effect of increasing concentrations of NaCl and C6H8O7 and NaHCO3 in the solutions were in different quantities depending on the polymer they affect, and this diversity and difference in the effect of the additives can be used in many fields such as those in the medical or industrial field, scientific research and oil fields.